LANGUAGE ENDANGERMENT IN INDONESIA - C. Ewing, Michael (UPI Press, 2014)
In Indonesia, language endangerment is primarily related to language shift. Data show that the most important symptoms of language shift and of the vitality of a language are number and quality of the domains in which it is used and transmitted. The second crucial symptom of language endangerment is the loss of transmission from one generation to the next. This is what is now being seen in many communities across Indonesia where children are no longer acquiring their parents’ language. There are two general endangerment scenarios that have occurred in Indonesia. The first is the immigration scenario in which members of another speech community from outside the area move in and due to economic and political advantage essentially ‘take over’ a local speech community, imposing their own language. The second is the emigration scenario in which members of a local speech community temporarily migrate outside of the community for education or work, and on returning bring the dominant language from outside into the community. Finally, we can now find in many parts of Indonesia that social changes including economic, educational, and political contexts, promote a shift from local to dominant language.